SISTEM PENENTUAN DAN PEMANTAUAN KUALITAS AIR BERSIH SUNGAI SABURAKE SEBAGAI AIR IRIGASI DI KELURAHAN TANJUNG MAS SEMARANG - Ririn Nurmandhani (STIKES Cendekia Utama Kudus, 2022)
Community in Tanjung Mas Village still lack of clean water, especially for watering plants on agricultural land. The Saburake River cannot be used as irrigation water because it was polluted by garbage and household waste. Based on the quality standard according to PP RI No. 82 of 2001, the results of laboratory tests of the water quality of the Saburake River showed moderate levels of contamination, there were several parameters that did not meet the requirements, total phosphate (1.16-1.19 mg/liter), COD (89, 7-92.8 mg/liter), BOD (35.7-52.3 mg/liter), DO (0.72-0.86 mg/liter), and total coliform (840,000-1,300,000 total/100ml ). So it took a tool to be able to purify water by means of filtration, as well as a water sensor to determine the level of turbidity of the water. Filtration can separate articles physically, chemically, and biologically to separate or filter out unsettled particles that are sedimented through a porous layer. The water sensor was used to measure the quality of clean water by considering the value of electrical conductive and conductive factor in real time. Based on the results of laboratory tests that have been carried out, it was found that the levels of Iron, Zinc, Lead, pH, and temperature were in accordance with the quality standards that had been set before the water went through the filtration process. The BOD5 level of the filtered water dropped from 30 mg/l in river water to 2.2 mg/l in the filtered water, and has met the maximum level for irrigation water. The COD level of river water is 75 mg/l and after the filtration process it drops to 28 mg/l, but when compared to the maximum level (3 mg/l) for irrigation water it still did not meet the standard. However, the water from the filtration process can already be used by the surrounding community to be used as irrigation water for the cultivation of Kelompok Wanita Tani Tunas Bahagia.